Effect of climate change on electricity demand and power generation of Bangladesh - Wares, S.M. Abrar Fahim; Hasan, Md. Mehedi; Islam, Md. Jihadul; Saleh, Syed Taha (BRAC Univeristy, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.